Low‐Voltage Operational, Low‐Power Consuming, and High Sensitive Tactile Switch Based on 2D Layered InSe Tribotronics. (8th February 2019) - Li, Mengjiao; Yang, Feng‐Shou; Hsiao, Yung‐Chi; Lin, Che‐Yi; Wu, Hsing‐Mei; Yang, Shih‐Hsien; Li, Hao‐Ruei; Lien, Chen‐Hsin; Ho, Ching‐Hwa; Liu, Heng‐Jui; Li, Wenwu; Lin, Yen‐Fu; et al.
Abstract: Electronics based on layered indium selenide (InSe) channels exhibit promising carrier mobility and switching characteristics. Here, an InSe tribotronic transistor (denoted as w/In InSe T‐FET) obtained through the vertical combination of an In‐doped InSe transistor and triboelectric nanogenerator is demonstrated. The w/In InSe T‐FET can be operated by adjusting the distance between two triboelectrification layers, which generates a negative electrostatic potential that serves as a gate voltage to tune the charge carrier transport behavior of the InSe channel. Benefiting from the surface charging doping of the In layer, the w/In InSe T‐FET exhibits high reliability and sensitivity with a large on/off current modulation of 10 6 under a low drain–source voltage of 0.1 V and external frictional force. To demonstrate its function as a power‐saving tactile sensor, the w/In InSe T‐FET is used to sense "INSE" in Morse code and power on a light‐emitting diode. This work reveals the promise of 2D material–based tribotronics for use in nanosensors with low power consumption as well as in intelligent systems. Abstract : A highly tactile‐sensitive (106 signal modulation) tribotronic transistor with a low operating voltage (0.1 V) and low power consumption is developed. The tribotronic transistor consists of the vertical combination of an In‐doped InSe transistor and triboelectric nanogenerator. This work demonstrates the promise of 2D material–based tribotronics for use in sensors and intelligent systems with low power consumption.